Implementasi Asas Kesederhanaan dalam Pemungutan Pajak Melalui Integrasi NIK dan NPWP sebagai upaya Peningkatan Penerimaan Pajak - Faturohman, Fatur (Uniku Law Review, 2023)
The aim of this research is to find out about the implementation of the principle of simplicity in tax collection in Indonesia. Tax collection by the government must be based on the principle of simplicity. The principle of simplicity means that the taxes collected by the government must be easy and understandable by the public. Currently, it is estimated that Indonesians have around 40 identity numbers, including taxpayer identification numbers. So, to achieve the principle of simplicity in tax collection, the government issued a policy regarding the integration of NIK and NPWP as one unit in managing tax administration. This research is normative legal research with a deeper understanding of secondary information in the form of literature reviews and related laws and regulations. The results of this research show that the application of NIK to NPWP as a means of tax administration has been regulated in Law Number 7 of 2021 concerning Harmonization of Tax Regulations, and Regulation of the Minister of Finance of the Republic of Indonesia No. 112/PMK.03/2022 with the policy of integrating NIK and NPWP, it will have the potential to increase the number of taxpayers in Indonesia, as well as tax revenues in Indonesia.